EXAME VESTIBULAR: providências relativas à inclusão de candidatos com deficiências - Rubia Carla Donda da Silva; Sandra Eli Sartoreto de Oliveira Martins (Revista de Políticas Públicas, 2018)
The development of inclusive policies and the commitment to universalize the basic education leaded to interventions guided to the expansion of the Higher Education. Thus, students with disabilities have started to plead vacancies in the Higher Education. Under those circumstances, we propose to investigate the rules which guide the entrance examinations in three Brazilian public uni- versities, in order to identity the explanations given to the disabled candidates concerning registration, test applying and correction. According to a theoreti- cal-documental approach, processing and analysis of the collected materials were inferred from the contributions of the theoretical approach to the sense production, proposed by Spink. Results showed restrictions in oﬀering specia- lized attendance to candidates with disabilities, as well as a lack of compliance to the educational recommendations and rules in force.